Provably Secure Online/Offline Identity-Based Signature Scheme Based on SM9. (30th March 2021) - Lai, Jianchang; Huang, Xinyi; He, Debiao; Wu, Wei
Abstract: SM9 is a Chinese cryptography standard, which includes a set of identity-based cryptographic schemes over pairings. SM9 identity-based signature scheme (SM9-IBS) was standardized by ISO/IEC and has been widely used in many real-world applications such as blockchain. Nevertheless, the signing algorithm of SM9-IBS suffers from several heavy calculations (e.g. pairings, scalar multiplications in groups), which might be a bottleneck for lightweight devices such as sensors. In this paper, we modify the SM9-IBS scheme slightly to support fast signing. In order to achieve this, we make the use of online/offline methodology and propose a new online/offline IBS scheme based on SM9. The proposed scheme is proved to be EUF-sID-CMA secure and is about 99% faster than SM9-IBS in terms of signature generation. Precisely, the time cost of online signing is <1 ms. Our scheme is appropriate for the Internet of Things. The theoretical analysis and demonstration show that the proposed scheme is comparable to existing efficient online/offline IBS schemes.